The field and temperature dependencies of the intra-grain and inter-grain critical current densities in (Tl0.5Pb0.5)(Sr0.8Ba0.2)(2)Ca2Cu3Ox ceramics - Senoussi, S; Kilic, A; Wivel, S; Grovenor, C (1995)
We report investigations of the magnetization and the associated critical current density of a Tl0.5Pb0.5)(Sr0.8Ba0.2)(2)Ca2Cu3Ox ceramic sample in T and H varying from 10(-2) to 7x10(4) Oe and 4.2 K to T-c approximate to 110 K. At high enough temperature, the M vs H relationship exhibits 5 different regimes reflecting various modes of penetration of flux through the material: (1) At H less than or equal to 2 Oe, the M(H) function is linear, reversible and controlled by the macroscopic demagnetizing factor N of the pellet. (2) As H is further increased one observes a tiny hysteresis cycle in a narrow field domain of about 40 Oe. (3) At still higher H and up to H-cl,H-g of the grains, the M(H) relationship becomes again linear and reversible but with a slope reduced by a factor of four as compared to the initial one. (4) For H>H-cl,H-g and up to the irreversibility line we observe the usual regime of strong irreversibility and deduce the inter-grain current density using a modified Bean model that accounts for the anisotropy.